How brain-computer interface technology may improve the diagnosis of the disorders of consciousness: A comparative study - Spataro, Rossella; Xu, Yiyan; Xu, Ren; Mandalà, Giorgio; Allison, Brendan Z.; Ortner, Rupert; Heilinger, Alexander; La Bella, Vincenzo; Guger, Christoph (Frontiers in Neuroscience, 2022)
Objective: Clinical assessment of consciousness relies on behavioural assessments, which have several limitations. Hence, disorder of consciousness (DOC) patients are often misdiagnosed. In this work, we aimed to compare the repetitive assessment of consciousness performed with a clinical behavioural and a Brain-Computer Interface (BCI) approach. Methods: For seven weeks, sixteen DOC patients participated in weekly evaluations using both the Coma Recovery Scale-Revised (CRS-R) and a vibrotactile P300 BCI paradigm. To use the BCI, patients had to perform an active mental task that required detecting specific stimuli while ignoring other stimuli. We analysed the reliability and the efficacy in the detection of command following resulting from the two methodologies. Results: Over repetitive administrations, the BCI paradigm detected command following before the CRS-R in seven patients. Four clinically unresponsive patients consistently showed command following during the BCI assessments. Conclusions: BCI active paradigms might contribute to the evaluation of the level of consciousness, increasing the diagnostic precision of the clinical bedside approach. Significance: The integration of different diagnostic methods leads to a better knowledge and care for the DOC.